2018
DOI: 10.1038/s41437-018-0109-7
|View full text |Cite
|
Sign up to set email alerts
|

A singular value decomposition Bayesian multiple-trait and multiple-environment genomic model

Abstract: Today, breeders perform genomic-assisted breeding to improve more than one trait. However, frequently there are several traits under study at one time, and the implementation of current genomic multiple-trait and multiple-environment models is challenging. Consequently, we propose a four-stage analysis for multiple-trait data in this paper. In the first stage, we perform singular value decomposition (SVD) on the resulting matrix of trait responses; in the second stage, we perform multiple trait analysis on tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Although the mixed-model methodology by the frequentist approach has several desirable characteristics [49], the adoption of Bayesian statistical inference for genetic evaluation in the breeding of crop species has shown to be advantageous. Bayesian models have been used since 1986 [63] and further exploited in recent years [2325,64,65] due to the great computational advancements and new methodological applications and elucidations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mixed-model methodology by the frequentist approach has several desirable characteristics [49], the adoption of Bayesian statistical inference for genetic evaluation in the breeding of crop species has shown to be advantageous. Bayesian models have been used since 1986 [63] and further exploited in recent years [2325,64,65] due to the great computational advancements and new methodological applications and elucidations.…”
Section: Discussionmentioning
confidence: 99%
“…Two types of MT models were implemented. Firstly, by performing single value decomposition (SVD) of the matrix of all phenotypes, as proposed by Montesinos-López et al (2019a), whereby each of the decomposed and uncorrelated vectors from all the traits were predicted as traits themselves using the same genomic models as for ST predictions. The predictions of vectors were then back-transformed to the original trait scales to derive the MT predictions per-trait.…”
Section: Methodsmentioning
confidence: 99%
“…Accuracy of GS for low heritability traits (e.g., grain yield) can also be significantly increased by multivariate models when a correlated highly heritability trait is available [88,92]. MT models can improve indirect selection due to increased genetic correlation estimates [23,73,93]. Montesinos-López et al [77] showed the higher the genetic correlation between traits, the higher the prediction accuracy and benefit of MT over single trait models.…”
Section: Multi-trait Modelsmentioning
confidence: 99%